Nurse-based monitoring and management of breakthrough pain in an acute pain relief and palliative care unit. Issue 4 (7th August 2016) - Mercadante, Sebastiano; Prestia, Giovanna; Casuccio, Alessandra
ABSTRACT: Objectives : To assess the nurses' performance in assessing, treating, and documenting breakthrough pain (BTP) in a palliative care unit where traditionally there is continuous training. Methods : The study was performed in an acute palliative care unit. Once a week, a research nurse examined the documentation regarding all the episodes of BTP registered in a specific pain chart, designed by the institutional nurse board, as part of the routine nurse activity. Results : The charts of 50 consecutive eligible patients (32 M/18 F), were analysed. The mean number of episodes/patient was 3.3 (SD 1.61; range 1–7). 166 episodes occurred. The main BTP pain intensity was 7.06 (SD 0.82). In 7 episodes, pain intensity was not evaluated at T0. The pain intensity after 15 minutes after BTP medication was 3.01 (SD1.19). In 28 episodes, pain intensity was not evaluated at T15. The change in pain intensity was highly significant (P < 0.0005). BTP episodes were distributed normally through different day intervals. No relevant adverse event attributable to BTP medication was reported in the nurse diary. Conclusion : Training in a research environment allows a good nurse capability in evaluating and treating BTP, and above all, providing documentation for each BTP episode. The theoretical work and recommendations around BTP need to be translated into day-to-day clinical practice.